Developing a sustainable urban landscape management system for Kabul, Afghanistan - Darkhani, Faiza (2019)
Urban landscape plays a significant role in the quality of life and sustainability issues of urban development. As more new cities and metropolitan areas are created and more money spent on urban landscapes, it is becoming more urgent to discover an urban landscape management scheme that addresses these issues. At the same time landscape management plays a key role in improving the quality of urban landscape. High quality urban landscape management requires a proper management system. In rapidly urbanizing cities, such as Kabul in Afghanistan, the importance of urban landscape and green space is acknowledged. However, due to the rapid urbanization and population growth, managing the city’s landscape is a major challenge. Developing countries like Afghanistan are facing a decline in green spaces due to lack of proper management. The objective of this study is to propose a sustainable urban landscape management framework for Kabul in Afghanistan. Three countries were selected as case studies – Malaysia, Singapore, and England. Their urban landscape management systems were studied. Relevant professionals and experts in Kabul were interviewed to elicit their views regarding urban landscape management in the city, and their comments on the proposed management framework are discussed. The findings of the research confirm that the framework has considerable potential for improving the urban landscape management in Kabul Afghanistan. It is hoped that the findings of this study will increase the local authority’s knowledge in managing the urban landscape and thereby, decreasing the deterioration and decline of urban green spaces in Kabul’s urban landscape.